2017
DOI: 10.1021/acs.jpcc.6b11952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Heating on the Crystallization of Glutathione Tripeptide on Silver Nanoparticle Films

Abstract: Effect of microwave heating on the crystallization of glutathione (GSH) tripeptide using the metal-assisted and microwave-accelerated evaporative crystallization (MA-MAEC) technique is reported. GSH crystals were grown from supersaturated solutions of GSH (300–500 mg/mL) on the iCrystal plates with silver nanoparticle films (SNFs) and without SNFs in three different microwave systems operating at 2.45 GHz: conventional (multimode, fixed power at 900W), industrial (monomode, variable power up to 1200 W), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In response to the limitations of current methods of crystallization, the Aslan Research Group has previously presented a method, called the metalassisted and microwave-accelerated evaporative crystallization (MA-MAEC) technique, which promotes the rapid and high-throughput crystallization of amino acids (i.e., alanine, glycine, arginine) [15][16][17], peptides (i.e., glutathione) [18], and proteins (i.e., lysozyme) [8,14]. The MA-MAEC technique was proven to increase the growth rate of crystallization in a shortened period while producing crystals that allow for analysis through diffraction screens [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the limitations of current methods of crystallization, the Aslan Research Group has previously presented a method, called the metalassisted and microwave-accelerated evaporative crystallization (MA-MAEC) technique, which promotes the rapid and high-throughput crystallization of amino acids (i.e., alanine, glycine, arginine) [15][16][17], peptides (i.e., glutathione) [18], and proteins (i.e., lysozyme) [8,14]. The MA-MAEC technique was proven to increase the growth rate of crystallization in a shortened period while producing crystals that allow for analysis through diffraction screens [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments utilizing the MA-MAEC technique yield fully developed crystals with the use of a conventional microwave system (multi-mode, fixed power at 900 W), industrial microwave (monomode, variable power up to 1200 W), and the iCrystal system (mono-mode, variable power up to 100 W). However, to optimize the technique, a comparative analysis of the efficiency of available microwave technology revealed that the iCrystal system rapidly produced the largest high-quality crystals with uniform size distribution within the shortest period [18].…”
Section: Introductionmentioning
confidence: 99%